Long‐term use of proton pump inhibitors and prevalence of disease‐ and drug‐related reasons for gastroprotection—a cross‐sectional population‐based study. Issue 1 (16th November 2016) - Wallerstedt, Susanna M.; Fastbom, Johan; Linke, Johannes; Vitols, Sigurd
Abstract: Purpose: To analyse the prevalence of long‐term use of proton pump inhibitors (PPI) with respect to underlying diseases and drugs, and to find predictors for such treatment when an evident rationale for the PPI treatment is lacking. Methods: The study cohort consisted of individuals, ≥65 years in 2010, residing in the Region Västra Götaland during 2005–2010. For individuals with and without long‐term use of PPI in 2010, we investigated the prevalence of an underlying diagnosis, that is, an acid‐related disease during the five preceding years, as well as concomitant long‐term use of antiplatelet agents or cyclooxygenase inhibitors. Results: In all, 278 205 individuals (median age: 74 years; 55% female; median 3 drugs per person; 5% nursing home residents, 11% with multi‐dose drug dispensing) were included in the analyses, 32 421 (12%) of whom were on long‐term treatment with PPI in 2010. For 12 253 individuals (38%) with such treatment, no underlying rationale was found. In individuals without a disease‐ or a drug‐related reason for PPI use, nursing home residence, number of drugs, female sex, but not multi‐dose drug dispensing, were associated with long‐term use of PPI; adjusted odds ratios (95% confidence interval): 1.63 (1.49; 1.78), 1.27 (1.26; 1.28), 1.24 (1.19; 1.29), and 0.94 (0.88; 1.01), respectively. Conclusions: Long‐term use of PPI occurs in one out of nine individuals in the older population. For four out of ten of these, no reason for PPI use can be identified. Nursing home residence, female sex, and greater number of drugs predict non‐rational long‐term use of PPI. © 2016 The Authors. Pharmacoepidemiology and Drug Safety published by John Wiley & Sons Ltd.